The use of maize haploidy inducers as a tool in agricultural plant biotechnology - A. V. Ulyanov; A. V. Karlov; E. B. Khatefov (Вавиловский журнал генетики и селекции)
The discovery of the ability of some mutations to stimulate haploidy during hybridization made it possible to create one of the most promising and sought-after trends in the field of reproductive biology. Haploid inducers created on their basis are capable of increasing the frequency of haploidy up to 15 %. The improvement of the existing haploid inducer lines and the search for new genes that contribute to a high frequency of haploidy are underway. Along with these studies, the field of application of haploid inducers in genetics and plant breeding is expanding. Haploid inducers carrying R1-nj genes for anthocyanin pigmentation of the seed and embryo are able not only to mark the hybrid embryo and identify haploid genotypes, but also to detect genes that suppress the anthocyanin color of the grain, like C1-I, C2-Idf, and In1-D. Depending on their quantity, the phenotypic manifestation of the gene in the seed varies. Haploidy is widely used for accelerating hybrid breeding and obtaining both new maize lines with improved traits and their sterile counterparts. By introducing certain genes into the genome of the improved line, breeders can use the doubled haploid (DH) breeding technology to accelerate the creation of pure lines carrying the desired gene. Haploid inducer maize lines and their tetraploid analogs are used in the selection of rediploid maize lines by their resynthesis from tetraploid genotypes. In 2019, Syngenta Company synthesized a haploid inducer maize line carrying a CRISPR/cas construct capable of simultaneously stimulating haploidy and editing the genome at a specified DNA site. Thanks to this technology, it became possible to improve haploid inducers by introducing various CRISPR/cas constructs into the haploid inducer genome for editing any DNA site. Maize haploid inducers are widely used in doubled haploid wheat breeding. The first experiments showed that the most effective haploid inducer for stimulating haploidy in wheat is maize pollen. Researchers are intensively searching for other ways of using maize haploid inducers in plant breeding.